2018
DOI: 10.1093/dote/doy072
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between extralaryngeal endoscopic findings, proton pump inhibitor (PPI) response, and pH measures in suspected laryngopharyngeal reflux

Abstract: Laryngopharyngeal reflux (LPR) is a clinical entity diagnosed by history laryngoscopic findings that has a variable response to empiric proton-pump inhibitor (PPI) therapy. While the reflux finding score (RFS), an endoscopic scoring scheme, has been advanced as a measure of LPR, it has not been externally validated against symptom severity in practice. Extralaryngeal pharyngeal endoscopic findings may have diagnostic utility but remain underexplored. This study assesses the correlation between extralaryngeal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…These results support the further consideration of oral and pharyngeal findings in the clinical evaluation of LPR patients at baseline (clinical diagnosis) and throughout treatment. Similar conclusions have been made in the study by Agrawal et al, who, however, did not formally investigate the evolution of extralaryngeal findings throughout treatment 34 . Moreover, the improvement of findings seems to vary with regard to the anatomical area and probably the histological pattern of mucosa.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These results support the further consideration of oral and pharyngeal findings in the clinical evaluation of LPR patients at baseline (clinical diagnosis) and throughout treatment. Similar conclusions have been made in the study by Agrawal et al, who, however, did not formally investigate the evolution of extralaryngeal findings throughout treatment 34 . Moreover, the improvement of findings seems to vary with regard to the anatomical area and probably the histological pattern of mucosa.…”
Section: Discussionsupporting
confidence: 71%
“…Similar conclusions have been made in the study by Agrawal et al, who, however, did not formally investigate the evolution of extralaryngeal findings throughout treatment. 34 Moreover, the improvement of findings seems to vary with regard to the anatomical area and probably the histological pattern of mucosa. Laryngeal findings improve more slowly than extralaryngeal findings, which have been underexplored in LPR.…”
Section: Discussionmentioning
confidence: 99%
“…The search identified 1355 relevant papers, of which 76 studies met the inclusion criteria, accounting for 6457 patients. A total of 64 studies consisted of empirical therapeutic trials (Table 1)[8-72], and 12 were studies where authors formally identified LPRD with pH-monitoring ( n = 10) or MII-pH ( n = 2) (Table 2)[40,56,60,73-83].…”
Section: Resultsmentioning
confidence: 99%
“…Another study focused on the correlation results of laryngopharyngeal pH testing and clinical findings during laryngoscopy. A significant correlation could not be found, however again only a small number of patients ( n = 33) was included in the study and trends approaching statistical significance were noted[ 27 ]. In addition, Yadlapati et al [ 28 ] investigated the correlation between laryngopharyngeal pH testing and PPI response and found no significant correlation.…”
Section: Discussionmentioning
confidence: 99%